ROS-balancing-engineered bio-heterojunction hydrogel accelerated the infected bone regeneration based on Sono-chemo dynamic therapy - Jiani Xu; Fanshangming Zhou; Lingyan Cao; Huilin Wang; Jiani Hu; Shuo Qiu; Yulan Liu; Yan Zhang; Jie Wang; Xinquan Jiang (Bioactive Materials)
Hypoxic deep-seated infections in refractory environments impede wound healing and exacerbate antibiotic resistance. Sonodynamic therapy (SDT) shows promise in combating pathogenic bacteria; however, the excessive reactive oxygen species (ROS) generated during the process often induce severe inflammatory responses, hindering tissue regeneration. To overcome these limitations, we have developed a multifunctional hydrogel, inspired by the dynamic regulatory mechanisms of rhizobia. GSH-SF/PeMA/MXene-TiO2 (SP-MT) hydrogel was synthesized through the thiol-ene click chemistry mechanism. Methacrylated pectin (PeMA) and GSH-modified silk fibroin (GSH-SF) were combined with MXene-TiO2 addition. This hydrogel exhibited favorable injectability, mechanical properties, swelling and degradation performance. In addition, this hydrogel can employ ultrasound-triggered dynamic ROS modulation to enable spatiotemporal regulation of antibacterial activity and promote tissue regeneration, effectively addressing the dual challenges of infection management and oxidative stress. Under ultrasound stimulation, SP-MT hydrogel can rapidly eradicate bacteria by disrupting membrane integrity and electron transport chains (ETCs) while simultaneously generating substantial ROS. Once the ultrasound stimulation ceased, the hydrogel and its degradation products eliminated residual ROS. In vivo studies further demonstrated that the nanohydrogel can accelerate soft tissue regeneration and periodontal bone regeneration by eradicating bacterial biofilms, promoting angiogenesis, and activating the TGF-β/SMAD signaling pathway. Therefore, this work introduces a novel strategy for equipping hydrogels with programmed antibacterial and anti-inflammatory functionalities, providing an innovative solution for treating deep-seated infections, particularly in periodontitis therapy.